OUTCOME OF PRIMARY REPAIR OF VESICOVAGINAL FISTULA (VVF) - Muhammed khalid; Muhammad Hammad Hassan; Muhammad Asif; Qadeer Ahmad Tariq (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE:  Vesicovaginal fistula is one of the common gynecological problems faced by ladies in developing countries on account of certain significant lacunas in the healthcare delivery system and lack of awareness. The purpose of this study is to highlight our experience of primary vesicovaginal fistula repair.METHODOLOGY: It is a cross-sectional experimental study from February 2019 to February 2020. Nineteen consecutive patients having vesicovaginal fistulas up to 3 cm in size, single in number were included in the study while those having fistulas more than 3 cm, involving urethra, bladder neck, and ureteric orifice were excluded. After a detailed history, physical examination, laboratory workup, and cystoscopic examination under anesthesia, the fistulas were repaired. All information was noted on the pre-planned questionnaire for this purpose.RESULTS: There are around 63% of patients having fistula infratrigonal and the rest percentage on the supratrigonal area of the urinary bladder. The risk factor found hysterectomy in 32% of patients, unsupervised home delivery in 16% of patients, C-Section in 12% of patients, delivery by an untrained person in 26% of patients, induced miscarriages in 5% of patients, and other risk factors found in 12% patients. The 68% of patients managed through transabdominal and the rest 32% patients operated through the transvaginal approach. The surgery, either transabdominal or transvaginal, was successfully done in 84% of patients and failed in the rest of 16% of patients.CONCLUSION: Fistulas due to obstetric trauma were mostly preventable. The success of surgical repair was due to health professionals' expertise, the suitable decision about approach, method of repair, proper preoperative evaluation, and careful postoperative management.